MODELING OF THE ARTIFICIAL BLOOD CHAMBER AND THE MICROPUMPS PULSATILE DRIVE FOR BLOOD TRANSFUSION - Bartel, Sebastian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This article presents examples of laminar blood flow and pulsatile blood flow devices for human heart assist and the total artificial hearts. The presented examples of these heart assist devices were considered for modeling the shape of the artificial blood chamber, and the electromagnetic drive of these devices. This article describes the general principle of artificial heart devices and his advantages and disadvantages resulting from the construction.